Establishing the cost of implementing a performance-based, managed entry agreement for a hypothetical CAR T-cell therapy. Issue 1 (1st January 2018) - Kefalas, Panos; Ali, Omar; Jørgensen, Jesper; Merryfield, Nick; Richardson, Tim; Meads, Adam; Mungapen, Laura; Durdy, Matthew
ABSTRACT: Background : Market access stakeholders consider the adoption of Managed Entry Agreements (MEAs), however a clearly described methodology to quantify their implementation burden is not available in the public domain. Objective : To quantify the cost of implementing a performance-based MEA at the hospital level. Methods : The analysis involved a hypothetical one-off therapy targeting Acute Lymphoblastic Leukaemia. Data collection from five NHS Hospital Trusts in England captured costs by task, job band, personnel time and capital investment. We compared the administrative burden of the standard of care (SoC) to that of adopting the therapy with or without an MEA over 10 years. Findings : The 10-year cost for the activities required to support hospital payments for the target patient population in England varied as follows: for the SoC was £447, 353, compared to £1, 117, 024 for the novel therapy with MEA, and £245, 317 without MEA. Conclusions : The higher cost associated with the SoC compared to the novel therapy without an MEA, arises from the higher frequency of infusions requiring payments and the associated mandatory data capturing requirements for oncology therapies. The novel therapy with MEA presents the greatest burden due to increased frequency of monitoring in year one to compensate for the greater uncertainty in clinical data and to inform the performance-based reimbursement.